The Influence of Social Media Marketing on Consumer Purchase Intention in Fashion Stores on the Shopee Platform: The Mediating Role of Consumer Trust - Erma Yusida; Bambang Septiawan; Nisa Fitriani (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This quantitative cross-sectional study investigates the influence of social media marketing on consumer purchase intention in fashion stores on the Shopee platform, with consumer trust as a mediating variable. Data were collected through an online questionnaire from respondents from Blitar city who had recent experience purchasing fashion products on Shopee. Social media marketing was measured through indicators such as attractive content, two-way interaction, trend updates, personalization, and electronic word-of-mouth. Consumer trust was assessed using competence, benevolence, and integrity dimensions, while purchase intention was evaluated based on intention to buy soon, serious consideration after viewing posts, and preference over other platforms. The data were analyzed using SPSS for validity, reliability, and classical assumption tests, and Hayes’ PROCESS macro for mediation analysis. The results revealed that all hypotheses were supported. Social media marketing had a positive and significant effect on consumer trust and on purchase intention. Consumer trust significantly influenced purchase intention and partially mediated the relationship between social media marketing and purchase intention. Theoretically, the study advances the Stimulus-Organism-Response framework and trust-transfer theory in the context of Indonesian social commerce. Practically, the findings recommend that fashion store owners prioritize high-quality visual content, responsive engagement, authentic testimonials, and personalized recommendations to build trust and enhance purchase intention on Shopee.